Pengaturan Pertanggungjawaban Pidana Korporasi dalam Undang-Undang Nomor 45 Tahun 2009 Tentang Perikanan - Maria Elviana Lelangwayan; Aksi Sinurat; Orpa Ganefo Manuain (Pusat Riset dan Inovasi Nasional, 2025)
Law Number 31 of 2004 concerning Fisheries as amended by Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries recognizes corporations as subjects of criminal acts in criminal acts in the fisheries sector, but the corporations are not held criminally responsible.This research is a normative legal research, using a statutory approach and a conceptual approach with literature study techniques or document studies. The processing of legal materials is carried out with several processes, namely the validity of legal materials, classification of legal materials, recording legal materials and analysis of legal materials. Analysis of legal materials is carried out in a normative qualitative juridical manner with descriptive and prescriptive analysis. The results of this study indicate first, the regulation of corporate criminal liability in the current Fisheries Law still has shortcomings/weaknesses, namely it does not clearly formulate when a corporation is said to have committed a crime and based on the history of the development of corporations as subjects of criminal law, corporate criminal liability in the current Fisheries Law is still at stage II where corporations are recognized as perpetrators of criminal acts, but their criminal liability has not directly affected the corporation and only the corporate administrators are responsible. Second, the regulation of corporate criminal liability in the future can be seen in the Fisheries Bill which has answered the weaknesses/deficiencies in the Fisheries Law and has accommodated corporate criminal liability where corporations can be subject to principal or additional criminal sanctions for the crimes they commit.